Single-cell RNA sequencing of peripheral blood reveals immune cell dysfunction in premature ovarian insufficiency - Zhang, Caihong; Yu, Dong; Mei, Yue; Liu, Shanrong; Shao, Huijing; Sun, Qianqian; Lu, Qiong; Hu, Jingjing; Gu, Hang (Frontiers in Endocrinology, 2023)
Background: Premature ovarian insufficiency (POI) is one of the most common causes of female infertility and the etiology is highly heterogeneous. Most cases are idiopathic and the pathogenesis is unclear. Previous study proved that immune system plays a crucial role in ovarian physiology. However, the precise immune process remains unclear. This study aim to analyze the characteristics of peripheral blood mononuclear cells (PBMC) from POI through single-cell RNA sequencing (scRNA-seq) and to explore the potential immune response mechanism of idiopathic POI. Result :, A total of 22 cell clusters and 10 cell types were identified in two samples. Compared with normal control, the percentage of classical monocytes and NK cells were decreased, plasma B cells were increased and the CD4:CD8 ratio was significantly higher in POI. Furthermore, DEG analysis revealed both known and novel markers for the main cell types, including upregulation of IGHM, IFITM1, CD69, JUND and downregulation of LYZ, GNLY, VCAN and S100A9, which enriched in NK cells mediated cytotoxicity, Antigen processing and presentation, IL-17 signaling pathway. Among them IGHM and LYZ were the most significant up-regulated and down-regulated gene throughout all the cell clusters of POI.As last the strength of cell-cell communication differed between the HC and POI, with multiple signaling pathways being identified. The TNF pathway was found to be unique to the POI, with CD16+ monocytes being the major receivers and senders of TNF signaling.